RATERS’ FATIGUE AND THEIR COMMENTS DURING SCORING WRITING ESSAYS: A CASE OF IRANIAN EFL LEARNERS - Mahshanian, Amir; Eslami, Abbas Rasekh; Ketabi, Saeed (Universitas Pendidikan Indonesia, 2017)
Rating accuracy in writing among EFL learners is crucial in determining their English proficiency. Despite the importance of its accuracy, little is known about various factors may affect the accuracy of rating writing essays. This study examines how raters’ comments on EFL writing tasks change as a result of fatigue. To this end, four raters were selected and each given 28 essays to score and comment on. Six general types of raters’ comments (i.e., those on grammar, choice of words, organization, punctuation, dictation, and capitalization) were into focus in this study. Overall, results suggested that fatigue affects raters’ frequency of comments on grammar, choice of words, and organization, and that raters’ comments on punctuation, dictation, and capitalization do not seem to change significantly due to the effect of fatigue. Furthermore, this study revealed that the most and least frequent comments in 112 scored essays were those on grammar and dictation, respectively.